Hubungan Dukungan Keluarga Dengan Kepatuhan Minum Obat Pasien Skizofrenia Di Poli Jiwa RSUD dr. Murjani Sampit - Putria Carolina; Melisa Frisilia; Desriati Desriati (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Schizophrenia is a serious mental disorder that affects the way an individual thinks, feels, and behaves. Family, as a source of support, is crucial for individuals with schizophrenia as an essential aspect of the recovery process. This support includes overseeing medication intake, providing continuous and optimal care, and empowering individuals with schizophrenia. The issue observed at the Mental Health Clinic of the Regional General Hospital dr. Murjani Sampit is the insufficient family support in accompanying patients for check-ups, leading to many patients experiencing relapses due to inadequate adherence to regular medication intake. This study aims to determine the relationship between family support and medication adherence in patients with schizophrenia at the Mental Health Clinic of RSUD dr. Murjani Sampit. The research design used is correlational with a cross-sectional approach. The instrument used is a questionnaire, and statistical analysis is performed using the Spearman's rho test. The sample consists of family members of patients, totaling 68 individuals. Statistical analysis with Spearman's rho shows a p-value of 0.000, where (α < 0.05), indicating that H1 is accepted, meaning: "There is a relationship between family support and medication adherence in patients with schizophrenia at the Mental Health Clinic of RSUD dr. Murjani Sampit." The conclusion of this study is that family support becomes a significant factor influencing individuals' beliefs and health values, as well as determining the treatment programs they will receive. Families also play a crucial role in providing support and making decisions regarding the treatment of their ill family members.